Enhancing Oral Proficiency Using Three Steps Interview Technique for Eleventh Graders - Dhena Usthiana Haryanti; Rohmati Nur Indah; Sri Wahyuni (Journal of Languages and Language Teaching, 2021)
Enhancing students' abilities and potential is an important thing that every teacher must do gradually. The ability to speak in a foreign language is one of the skills that must be developed, which will benefit students in their learning process. The aim of this study is to enhance students' oral proficiency using Three steps interview technique for eleventh-grade students. Quasi-Experimental research design as a method applied in this study, to determine whether students are learning to use the technique Three Steps Interview has the ability to speak that better than the students who are taught using the technique of group discussion. This research involves two classes divided into an experimental class and a control class with 32 students in each class. Students received special treatment in the experimental class, namely, using the Three Steps Interview technique, while in the control class, the researcher applied the Group Discussion technique. The instrument used in testing students' oral proficiency was using a pretest before implementing learning techniques in each class and doing a posttest after applying learning techniques. The data analysis results showed that p(0.000)< significance level (0.05), which means that Three Steps Interview has significant effect as cooperative learning on oral proficiency, motivation and enthusiasm during the learning process. Thus, students can easily express their ideas and opinions confidently.